Characteristics of the cases diagnosed as depression after consultation in a university hospital - Kologlu, M.; Tezcan, E.A.; Ulkeroglu, F.; Culha, F.; Karabulut, C. (My University, 1999)
Thinking of human as biopychosocial in current general medical management increases the importance of psychiatric consultation. The aims of our study were to determine the sociodemographic and clinical features, the reasons of consultation, the cases of primary or secondary depression associated with physical disease in patients diagnosed as depression after consultation in clinics except psychiatry. Our study group included 42 patients consulted during the period of January-April 1996 and diagnosed as depressive disorder according to the DSM-III-R criteria. All data about the patients and reasons for consultations were noted using a special form for every patients. We observed that consultations were mostly required by Internal Disease and Chest Disease Clinics. The reasons for consultation were diagnostic difficulty, observed psychiatric symptoms and the history of suicide attempt. And also we observed that depressive disorders attending with somatic complaints were admitted clinics except psychiatry and they caused the diagnostic diffuculties and confusions in these clinics. At the end of our study, the result that established the importance of psychiatric consultations in diagnosing and treatment of patients were obtained.
Bir universite hastanesinde konsultasyonla depresyon Tanisi alan vakalarin ozellikleri
Keywords: Consultation; Depression